2005
DOI: 10.1177/0092070305275249
|View full text |Cite
|
Sign up to set email alerts
|

Control Systems' Effect on Attributional Processes and Sales Outcomes: A Cybernetic Information-Processing Perspective

Abstract: Built upon a cybernetic information-processing framework, this article advances and empirically tests a conceptual model proposing the relationships between sales controls (outcome, activity, capability), salespeople's attributional ascriptions (effort, strategy, ability), attributional dimensions (internal/external, stable/unstable), and psychological consequences (job satisfaction, performance expectation Sales performance is a function of how salespeople adapt and adjust to successes and failures within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 62 publications
1
44
0
3
Order By: Relevance
“…In keeping with this contention, output controls have been found to increase salespeople's attributions that effort expenditures are needed for goal achievement. Control systems that emphasize end results increase salespeople's awareness of sales expectations by providing feedback showing that outcomes and effort are important (Fang et al 2005a). Hence, output controls not only provide achievement standards but instruct salespeople to increase their efforts, with the presumed result of improved sales performance.…”
Section: Output Controlsmentioning
confidence: 99%
“…In keeping with this contention, output controls have been found to increase salespeople's attributions that effort expenditures are needed for goal achievement. Control systems that emphasize end results increase salespeople's awareness of sales expectations by providing feedback showing that outcomes and effort are important (Fang et al 2005a). Hence, output controls not only provide achievement standards but instruct salespeople to increase their efforts, with the presumed result of improved sales performance.…”
Section: Output Controlsmentioning
confidence: 99%
“…Johnson (2006) employed bibliometrics in the use of this attribution theory and found that this theory has been adapted by a number of researchers such as DeCarlo (2005); Fang et al (2005). DeCarlo (2005) adapted this theory by integrating the attribution theory with persuasion theories to examine the impact of consumers' suspicion to the motives hidden by salesperson.…”
Section: Adaptation Of the Attribution Theorymentioning
confidence: 99%
“…Meanwhile Fang et al (2005) integrate the attribution theory with cultural theories to examine the relationship between sales control system (the outcome, activities, and capabilities), origin of sellers' attribution (attempts, strategies, and abilities), attribution dimensions (internal/external, permanent/temporary) and psychological consequences (work satisfaction, achievement expectation. They demonstrate that the control system differentially affects attribution processes across two cultures: U.S. and China.…”
Section: Adaptation Of the Attribution Theorymentioning
confidence: 99%
“…Most of the extant studies measure behaviour-based control strategies as a single construct. However, recent studies in sales control strategies show that behaviour-based control strategies comprise two different control types -activity control and capability control (Challagalla and Shervani, 1996 (Fang et al, 2005). Further, extant studies report numerous examples of how both activity control and capability control methods (e.g., D'Cruz and Noronha, 2007) are implemented in Indian call centres.…”
Section: Operationalising Managerial Control Approaches In the Servicmentioning
confidence: 99%